Study on Deformation and Permeation Properties of Gas-Containing Fractured Rock. (25th June 2019) - Yang, Yushun; Zhang, Dongming; Li, Shujian
Abstract : In this paper, we investigated the gas permeation properties of fractured rock during the process of stage load axial stress and cyclic load and unload confining pressure and come to some conclusions as follows: (1) the relationship between radial strain and deviatoric stress satisfied the quadratic polynomial function, and the relationship between permeability and deviatoric stress satisfied the exponential function under different axial stress levels; (2) in the staged load axial stress process, the axial strain-deviatoric curves of specimens conform to the quadratic polynomial function. The axial strain-deviatoric curves of specimens conform to linear function when confining pressure is 8.6 MPa or 2.0 MPa at different axial stress levels; (3) we used the permeability damage rate and maximum permeability damage rate to evaluate the recovery degree and reduction extent of permeability; (4) we used the volume expansion ratio and the maximum volume expansion ratio to evaluate the expansion degree and increase extent of rock samples' volume.